2003
DOI: 10.1016/s0028-3932(03)00118-0
|View full text |Cite
|
Sign up to set email alerts
|

Brain activation patterns during measurement of sub- and supra-second intervals

Abstract: The possibility that different neural systems are used to measure temporal durations at the sub-second and several second ranges has been supported by pharmacological manipulation, psychophysics, and neural network modelling. Here, we add to this literature by using fMRI to isolate differences between the brain networks which measure 0.6 and 3 s in a temporal discrimination task with visual discrimination for control. We observe activity in bilateral insula and dorsolateral prefrontal cortex, and in right hemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

38
315
4
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 428 publications
(361 citation statements)
references
References 57 publications
38
315
4
4
Order By: Relevance
“…The present findings also highlight the need for taking into consideration in further studies the differential effects across sensory modalities of attention modulation on temporal sensitivity. Our results are also in line with some neuroimaging evidence showing that different neural circuits are involved in processing sub-and suprasecond durations (Lewis & Miall, 2003;Tarantino et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The present findings also highlight the need for taking into consideration in further studies the differential effects across sensory modalities of attention modulation on temporal sensitivity. Our results are also in line with some neuroimaging evidence showing that different neural circuits are involved in processing sub-and suprasecond durations (Lewis & Miall, 2003;Tarantino et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…However, perhaps surprisingly, the asynchrony effects were consistently more pronounced in the left cerebellar hemisphere (i.e., ipsilateral to the premotor activation), although they were observed bilaterally at a lower statistical threshold of significance. This response profile might be explained by the specific role of the left cerebellum in temporal processing within the millisecond range, which is particularly relevant for audiovisual asynchrony detection in the current paradigm (17,18). Temporal processing along the motor hierarchy.…”
Section: Resultsmentioning
confidence: 93%
“…Indeed, this impression was statistically validated in a mixed design ANOVA of the integral with stimulus class (music vs. speech) as within-subject factor and group (musicians vs. nonmusicians) as between-subject factor, showing a main effect of group [F (1,35) (35) = 1.08, P = 0.14]. Furthermore, paired samples t tests comparing the temporal integration windows for speech and music in each group showed that musicians displayed a narrower temporal integration window for music relative to speech [t (18) = 4.29, P < 0.001], whereas the temporal integration windows for speech and music did not differ in nonmusicians [t (18) …”
Section: Resultsmentioning
confidence: 99%
“…Automatic timing processes include performance of a well-learned rhythm [17], control of the acceleration and deceleration of a learned sequential hand movement [18], or synchronous tapping to the beat of a rhythm [19,20] especially as performed by professional musicians [8]. Controlled timing processes include encoding of time duration [21,22], explicit discrimination of time intervals [23], on-line adjustment of the timing of motor or cognitive action [19,24,25], or those in early phases of rhythm learning [26].…”
Section: Reorganization Of Externally Guided Rhythmmentioning
confidence: 99%